Epilogue: Overview of Evaluation Strategy and Challenges - Knottnerus, J; Van Den Bruel, A; Buntinx, F (Wiley-Blackwell, 2009)
The first phase in the evaluation of diagnostic procedures consists of (1) specifying the clinical problem, the diagnostic procedures(s), and the research question, and (2) a systematic search and review of the literature, to decide whether the question can already be answered or whether a new clinical study is necessary. In preparing a new clinical study, the investigator must decide about the need for evaluation of (1) test accuracy in circumstances of maximum contrast or, as a further step, in the "indicated" clinical population; (2) the impact of the test on clinical decision making (3) prognosis; or (4) cost-effectiveness. The answers to these questions are decisive for the study design. Systematic reviews and meta-analysis, clinical decision analysis, cost-effectiveness analysis, and expert panels can help to construct and update clinical guidelines. Implementation of guidelines should be professionally supported and evaluated, in view of what is known about how clinicians approach diagnostic problems. Further developments in four fields are especially important: progress and innovation of (bio)medical knowledge relevant for diagnostic testing and its impact; the development of information and communication technology in relation to clinical research and practice; the changing role of the patient; and further exploration of methodological challenges in research on diagnostic problems. © 2009 Blackwell Publishing Ltd.